Residential Irrigation System Rainfall Shutoff Devices, or Rain Sensors - Michael D. Dukes; Dorota Z. Haman (EDIS)
Rain sensors—also called rain shutoff devices—are designed to interrupt the cycle of an automatic irrigation system controller when a specific amount of rainfall has occurred. They are small devices connected to the irrigation system controller and mounted in an open area where they are exposed to rainfall. This 3-page fact sheet is a minor revision that was Michael D. Dukes and Dorota Z. Haman, and published by the Agricultural and Biological Engineering Department, January 2017.